Autophagy Regulates Chromatin Ubiquitination in DNA Damage Response through Elimination of SQSTM1/p62 - Wang, Yanan; Zhang, Nan; Zhang, Luyao; Li, Ran; Fu, Wan; Ma, Ke; Li, Xue; Wang, Lina; Wang, Jiadong; Zhang, Hongquan; Gu, Wei; Zhu, Wei-Guo; et al. (Molecular cell, 2016)
Autophagy is an intracellular degradation system that delivers cytoplasmic constituents to the lysosome, and loss of autophagy has been linked to increased genome instability. Here, we report that loss of autophagy is coupled to reduced histone H2A ubiquitination after DNA damage. p62/SQSTM1, which accumulates in autophagy-defective cells, directly binds to and inhibits nuclear RNF168, an E3 ligase essential for histone H2A ubiquitination and DNA damage responses. As a result, DNA repair proteins such as BRCA1, RAP80, and Rad51 cannot be recruited to the sites of DNA double-strand breaks (DSBs), which impairs DSB repair. Moreover, nuclear-localized p62 increased the sensitivity of tumor cells to radiation both in vitro and in vivo, and this required its interaction with RNF168. Our findings indicate that autophagy-deficiency-induced p62 accumulation results in inhibition of histone ubiquitination and highlight the complex relationship between autophagy and the DNA damage response. [Display omitted] •Loss of autophagy leads to a deficiency of chromatin ubiquitination•Autophagy substrate p62 inhibits DNA-damage-induced histone ubiquitination•p62 directly inhibits RNF168 E3 ligase activity Wang et al. describe a role of selective autophagy in regulating chromatin ubiquitination during the repair of DNA double-strand breaks (DSBs). They found that the autophagy receptor and substrate p62/SQSTM1 inhibits DSB-induced histone and chromatin ubiquitination, which has a critical role in attracting key repair factors to the break sites.